2007
DOI: 10.1016/j.jmb.2006.11.090
|View full text |Cite
|
Sign up to set email alerts
|

Thermostability/Infectivity Defect Caused by Deletion of the Core Protein V Gene in Human Adenovirus Type 5 Is Rescued by Thermo-selectable Mutations in the Core Protein X Precursor

Abstract: SummaryMastadenoviruses represent one of the four major genera of the Adenoviridae family comprising a variety of mammalian pathogens including human adenovirus (Ad), whose genomes encode a gene for minor core protein V (pV), not found in other genera of Adenoviridae. Deletion of other genusspecific genes (gene IX and E3 genes) from Ad type 5 (Ad5) genome has been experimentally studied in vitro and the results on biological characterization of the mutants support the phylogenetic evidence of those genes being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 52 publications
(10 reference statements)
1
49
0
Order By: Relevance
“…A mutant adenovirus that lacks protein V (Ad5-dV) has reduced thermostability and infectivity, demonstrating that protein V plays a critical role in the generation of infectious particles (21). However, relatively little biochemical or structural information has been obtained for protein V. During the infection process, protein V is not released from the viral particles either when the virus penetrates the cells during infection (43) or upon heating purified particles (42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A mutant adenovirus that lacks protein V (Ad5-dV) has reduced thermostability and infectivity, demonstrating that protein V plays a critical role in the generation of infectious particles (21). However, relatively little biochemical or structural information has been obtained for protein V. During the infection process, protein V is not released from the viral particles either when the virus penetrates the cells during infection (43) or upon heating purified particles (42).…”
Section: Discussionmentioning
confidence: 99%
“…This deletion significantly disrupted viral assembly concomitant with alterations in the capsid morphology and a substantial reduction in thermostability and infectivity (21). Overall, these studies indicate that protein V has a critical role in capsid assembly and in the formation of infectious virions (21).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The role of core protein V is less certain, but it was recently shown that it is nonessential for virus viability, although the initial mutants produced were extremely thermolabile. Variants selected for greater thermostability showed mutations in core protein X, suggestive of an interaction between the two proteins (34). One copy of terminal protein is also bound to each end of the genome.…”
mentioning
confidence: 99%
“…It is not known if pV enters the nucleus on its own or in complex with other factors (143), or if it stays in the cytoplasm in association with the mitochondrial protein p32 implicated in ARFmediated apoptosis (144,145). Remarkably, a pV knock-out virus is viable in the presence of compensatory mutations in the mu protein (146). This suggests that pV has no unique functions in the replication cycle of mastadenoviruses, at least in cultured cells, which is further supported by the observation that pV does not occur in atadenoviruses, aviadenoviruses and siadenoviruses.…”
Section: Nuclear Import Of Adenovirus Dna Associated Proteinsmentioning
confidence: 99%